Phytochemical profile, enzyme inhibition activity and molecular docking analysis of Feijoa sellowiana O. Berg - Fatema R. Saber; Rehab M. Ashour; Ali M. El-Halawany; Mohamad Fawzi Mahomoodally; Gunes Ak; Gokhan Zengin; Engy A. Mahrous (Taylor & Francis Group, 2021)
Feijoa sellowiana leaves and fruits have been investigated as a source of diverse bioactive metabolites. Extract and eight metabolites isolated from F. sellowiana leaves were evaluated for their enzymatic inhibitory activity against α-glucosidase, amylase, tyrosinase, acetylcholinestrerase and butyrylcholinesterase both in vitro and in silico. Feijoa leaves' extract showed strong antioxidant activity and variable levels of inhibitions against target enzymes with a strong anti-tyrosinase activity (115.85 mg Kojic acid equivalent/g). Additionally, α-tocopherol emerged as a potent inhibitor of AChE and BChE (5.40 & 10.38 mmol galantamine equivalent/g, respectively). Which was further investigated through molecular docking and found to develop key enzymatic interactions in AChE and BChE active sites. Also, primetin showed good anti BChE (11.70 mmol galantamine equivalent/g) and anti-tyrosinase inhibition (90.06 mmol Kojic acid equivalent/g) which was also investigated by molecular docking studies.Highlights Isolation of eight bioactive constituents from Feijoa sellowiana leaves. In vitro assays using different enzymatic drug targets were investigated. In silico study was performed to define compound interactions with target proteins. Feijoa leaf is an excellent source of anti-AChE and antityrosinase bioactives.